2015
DOI: 10.4103/0974-7796.148637
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse large B-cell non-Hodgkin lymphoma of the prostate presenting with urinary outlet obstruction: A case report

Abstract: Large B-cell non-Hodgkin lymphoma involving the prostate accounts for 0.09% and 0.1% of non-Hodgkin lymphoma. We report a case of prostatic large B-cell non-Hodgkin lymphoma in a 77-year-old male with symptoms of urinary retention most probably due to benign prostate hyperplasia. He underwent multiple needle core biopsies through transrectal ultrasound of the prostate. Histopathological examination of the core biopsies revealed diffuse infiltration by atypical lymphoid cells in the prostatic stroma, which was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…4 In contrast, three of five patients treated with radiotherapy or radical prostatectomy had evidence of disease progression and died. 5 The R–CHOP regimen has shown improved disease-free survival in primary DLBCL compared to disease with nodal involvement or extensive disease. 5 …”
Section: Discussionmentioning
confidence: 99%
“…4 In contrast, three of five patients treated with radiotherapy or radical prostatectomy had evidence of disease progression and died. 5 The R–CHOP regimen has shown improved disease-free survival in primary DLBCL compared to disease with nodal involvement or extensive disease. 5 …”
Section: Discussionmentioning
confidence: 99%
“…PSA is produced by prostate epithelial cells, while prostate lymphoma is the source of mesophyll and PSA mostly in the normal range. However, Rao, RN et al indicated that nearly 20% of prostatic lymphoma patient with an elevation of PSA [3]. In the early stage, a small number of cases have reported the co-existence of non-hodgkin's lymphoma and prostate adenocarcinoma with an elevation of PSA [7].…”
Section: Discussionmentioning
confidence: 99%
“…Primary prostatic lymphoma is rare representing approximately 0.1% of all non-Hogdkin lymphomas which occur in men aged 60 years in average [1,2] Dysuria is the most common symptom of prostatic lymphoma, which can lead to misdiagnosis of benign prostatic hyperplasia and adenocarcinoma easily. Besides, PSA was widely considered in the normal range in most patients with prostatic lymphoma, only a few patients showed elevated [1,3]. At present, there is no consensus on the treatment but the recommended treatments included radiotherapy, chemotherapy and prostatectomy referring to the case report [4] We report a case of a 72-year-old primary prostatic diffuse large B-cell lymphoma patient with a significant increasing of PSA, developed CNS symptoms after completing a cycle of R-CHOP therapy.…”
Section: Introductionmentioning
confidence: 99%
“…However, confirmation of the diagnosis can be made by flow cytometry and immunohistochemical analysis of prostatic tissue [ 11 ]. Imaging modalities such as computed tomography and magnetic resonance imaging scans are often nonspecific for diagnosing DLBCL of the prostate [ 12 ]. PET is helpful in determining the metabolic 18 F-fluorodeoxyglucose activity in suspicious lesions and is useful in disease monitoring prior to and after treatments.…”
Section: Discussionmentioning
confidence: 99%